Production of Lentiviral Vectors Using a HEK-293 Producer Cell Line and Advanced Perfusion Processing - Tran, Michelle Yen; Kamen, Amine A. (Frontiers in Bioengineering and Biotechnology, 2022)
The field of lentiviral vector (LV) production continues to face challenges in large-scale manufacturing, specifically regarding producing enough vectors to meet the demand for treating patients as well as producing high and consistent quality of vectors for efficient dosing. Two areas of interest are the use of stable producer cell lines, which facilitates the scalability of LV production processes as well as making the process more reproducible and robust for clinical applications, and the search of a cell retention device scalable to industrial-size bioreactors. This manuscript investigates a stable producer cell line for producing LVs with GFP as the transgene at shake flask scale and demonstrates LV production in a 3L bioreactor using the Tangential Flow Depth Filtration (TFDF) as a cell retention device in perfusion mode. A cumulative functional yield of 3.3 x 1011 transducing units was achieved for a 2L working bioreactor volume and 16.3L of perfused media. In comparing to a previously published value that was achieved using the same stable producer cell line and the acoustic filter as the perfusion device at the same bioreactor scale, the TFDF perfusion run produced 1.5-fold higher cumulative functional yield. Given its scale-up potential, the TFDF is an excellent candidate to be further evaluated to determine optimized conditions that can ultimately support continuous manufacturing of LVs at large scale.